2016
DOI: 10.1159/000445875
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Down-Regulation of Glucocorticoid Receptor Gene Expression in the Dentate Gyrus after Acute Stress in vivo: Role of DNA Methylation and MicroRNA Activity

Abstract: Background: Although glucocorticoid receptors (GRs) in the hippocampus play a vital role in the regulation of physiological and behavioural responses to stress, the regulation of receptor expression remains unclear. This work investigates the molecular mechanisms underpinning stress-induced changes in hippocampal GR mRNA levels in vivo. Methods: Male Wistar rats were killed either under baseline conditions or after forced swim stress (FSS; 15 min in 25°C water). Rat hippocampi were micro-dissected (for mRNA, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 42 publications
3
35
0
1
Order By: Relevance
“…A 15‐min forced swim test in rats quickly resulted in lower levels of gr mRNA in the hippocampus, which was suggested to be a mechanism protecting neurons from repeated stress (Mifsud et al . ). The response to the social challenge observed in +F fish is similar suggesting that this could be a ‘normal’ vertebrate‐wide transcriptional response to challenging situations, which is disturbed by early rearing in a socially deprived environment, as seen in −F fish.…”
Section: Discussionmentioning
confidence: 97%
“…A 15‐min forced swim test in rats quickly resulted in lower levels of gr mRNA in the hippocampus, which was suggested to be a mechanism protecting neurons from repeated stress (Mifsud et al . ). The response to the social challenge observed in +F fish is similar suggesting that this could be a ‘normal’ vertebrate‐wide transcriptional response to challenging situations, which is disturbed by early rearing in a socially deprived environment, as seen in −F fish.…”
Section: Discussionmentioning
confidence: 97%
“…6 In animal models, stress has been shown to regulate activity in fully developed neural circuits, 40 and a recent study in rats found a decrease of Nr3c1 mRNA expression and an increase in both DNA methylation and Dmnt3a mRNA in the hippocampus within just 30 minutes of stress exposure. 41 These data suggest that epigenetics plays a dynamic role in the relationship between HPA axis dysregulation and psychopathology even outside of a developmental sensitive period. Given the need for epigenetic mechanisms in normal brain functioning, 42 we propose that stress-induced changes in cellular activity may translate into lasting perturbations in mood and cognition through activitydependent epigenetic mechanisms.…”
Section: Stress and Mddmentioning
confidence: 92%
“…For instance, and relevant for FS-associated processes, we discovered that GR expression is altered after a FS event as a result of DNA methylation changes and microRNA expression. Within 15 min of this stressful challenge, we found a significant reduction in GR mRNA expression, but not MR mRNA expression, specifically in the DG [59]. We found that forced swimming results in increased DNA methylation of the Nr3c1 gene associated with an enhanced binding of DNMT3A, which may explain the reduction in gene expression after stress.…”
Section: Histone and Dna Methylationmentioning
confidence: 70%
“…Forced swimming indeed evoked a significantly increased expression of mir124a in the DG, which was negatively correlated with the expression of GR mRNA expression. Using ChIP we investigated binding of GRs to a putative negative GRE within the Nr3c1 (GR) gene after FS to determine if GR was capable of suppressing its own expression, but no significant binding in this region was found [59]. These novel observations add to the complexity of regulatory mechanisms controlling GR expression and function in the brain.…”
Section: Histone and Dna Methylationmentioning
confidence: 99%